A national survey of intensive care follow-up clinics in Australia. Issue 6 (November 2020) - Cook, Katrina; Bartholdy, Roland; Raven, Monique; von Dohren, Gary; Rai, Sumeet; Haines, Kimberley; Ramanan, Mahesh
Abstract: Background: Intensive care follow-up clinics (ICFCs) have been implemented internationally with the aim to address the growing number of patients living with sequalae of critical illness and intensive care. However, data on Australian intensive care follow-up practice are rare. Objectives: The primary objective was to determine the proportion of Australian intensive care units (ICUs) that offer a dedicated ICFC to ICU survivors, with the intention of improving long-term outcomes of critical illness. Secondary objectives were to identify models of ICU follow-up and barriers to the implementation of ICFCs. Methods: A custom-designed, pilot-tested 12-question online survey was sent to the nurse unit managers and medical directors of all 167 Australian ICUs listed in the database of the Australian and New Zealand Intensive Care Society. Outcome measures included proportion of ICUs offering ICFCs, details on types of follow-up services with staffing, funding source, and reasons for not providing ICU follow-up. Results: One hundred seven of the 167 ICUs contacted responded to the survey. Of these, two (2%) operated a dedicated ICFC. Both ICFC s were nursing-led, with one receiving dedicated funding and the other being unfunded. Three units (3%) conducted routine outpatient follow-up by telephone; one of these services was doctor-led, and two were nurse-led. Four units (4%) were performing outpatient follow-up as part of research studies only. Among the units not operating an ICFC, the main reason given for not doing so were financial constraints (58%), followed by lack of clinical need (19%) and perceived lack of evidence (11%). Conclusion: In Australia, only two ICUs operated an ICFC. Only one outpatient follow-up service received dedicated funding, and financial constraints were the main reason given for units not offering outpatient follow-up services. Graphical abstract: Image 1